Self-Assembling Protein Surfaces for In Situ Capture of Cell-Free-Synthesized Proteins - Thornton, Ella Lucille; Paterson, Sarah Maria; Gidden, Zoe; Horrocks, Mathew H.; Laohakunakorn, Nadanai; Regan, Lynne (Frontiers in Bioengineering and Biotechnology, 2022)
We present a new method for the surface capture of proteins in cell-free protein synthesis (CFPS). We demonstrate the spontaneous self-assembly of the protein BslA into functionalizable surfaces on the surface of a CFPS reaction chamber. We show that proteins can be covalently captured by such surfaces, using ‘Catcher/Tag’ technology. Importantly, proteins of interest can be captured either when synthesized in situ by CFPS above the BslA surfaces, or when added as pure protein. The simplicity and cost efficiency of this method suggest that it will find many applications in cell-free-based methods.